‘The Research is Conducted…’: An Exploration of a Grammatical Metaphor Syndrome in Indonesian Research Articles - Ayomi, Putu Nur; Dreyfus, Shoshana; Hadi, Syamsul; Sutrisno, Adi (Lingua Cultura, 2020)
This article examines the use of one grammatical metaphor (hereafter GM) syndrome frequently found in Indonesian written language. This syndrome follows the lexicogrammatical structure of Process+Range or Process+Medium. Informed by Systemic Functional Linguistics (hereafter SFL), this study focuses specifically on Indonesian language research articles (hereafter RAs) as these have not been explored much in relation to GM. While GM typically increases the lexical density of a clause by condensing meaning into nominal groups, this GM syndrome seems to do the opposite. For example, rather than writing merubah ‘changed’ as the lexicogrammatical structure of Process, writers use melakukan perubahan ‘do some changes’, which has the lexicogrammatical structure of Process + Range. This has the effect of delexicalizing the verb as well as increasing the number of words in the clauses. Instead of seeing this form as a mere ritual in academic writing, this article seeks to understand the functional role of this form in academic articles. The analysis was conducted with a metafunctional lens, examining the ideational, interpersonal and textual functions of this form of GM through a systematic analysis of small corpus of journal articles from two refereed Indonesian humanities journals. The analysis reveals that ideationally, the GM syndrome is a resource to manage technicality, abstraction, taxonomy and activity sequence; textually, the syndrome is a resource organizing textual coherence through the management of hyperThemes; and interpersonally, the syndrome functions as a resource for Graduation, which decreases the force of propositions.